Geometry Optimization of PET Regrind Plastic Dust Separator Machine - Moh. hartono; R.N. Akhsanu Takwim; Subagiyo Subagiyo; Etik Puspitasari; Nila Alia; Radhi Nurvian Amrullah (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
This study aims to analyze the effect of various operational factors on the weight of dust collected by a dust collector machine. Using a multilevel factorial design, this study evaluates the interaction between frequency (Hz), hose length (m), and tube height (m). Analysis of variance shows that all three factors have a significant effect on the dust weight response (P-Value <0.05). The regression model with an R² of 99.15% shows a very high prediction accuracy. Parameter optimization was carried out to maximize the weight of dust collected, resulting in optimal conditions at a frequency of 50 Hz, a hose length of 2 m, and a tube height of 0.3 m with a dust weight of 72.75 g.